Microbial contamination of orthodontic buccal tubes from manufacturers. - Purmal, K.; Chin, S.; Pinto, J.; Yin, W.; Chan, K. (MDPI, 2010)
This study aimed to test the sterility of new unused orthodontic buccal tubes received from manufacturers. Four different types of buccal tubes were used straight from the manufactures package without any additional sterilizing step. Of these buccal tubes tested, three genera of bacteria, implicated as opportunistic pathogens, namely Micrococcus luteus, Staphylococcus haemolyticus and Acinetobacter calcoaceticus were recovered from these buccal tubes. Our data showing microbial contamination on buccal tubes highlights the need of sterilization before clinical use. We also suggest that manufacturers should list the sterility state of orthodontic buccal tubes on their packaging or instructions stating the need for sterilization.